ISLAM DAN DEMOKRASI - Wahyuni, Wahyuni (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2014)
Islam is believed to be a revealed religion, which covers all aspects of life. Muslims all over the world nowadays face many obstacles, both religious and worldly ones. One of them is the issue of Islamic politics, which further fall apart into two streams, the relation between ratio and revelation and between politics and religion. Indeed, both have interconnection. Democracy as one part of western political system has found it place within the development of political thought and globalization, which further shows its close relation with Islam.